Health Seeking Behaviour in Patients of Suppurative Otitis Media in Surat City - Rakesh Kumar; Ajay J Panchal (Medsci Publications, 2018)
Introduction: Perforation of tympanic membrane or cholesteatoma and pus discharge from ear characterize Suppurative Otitis Media (SOM). Apart from causing ear discharge and decreased hearing it can progress to cause life threatening complications. Early health seeking behaviour is mandatory. A number of barriers prevent early presentation at health facilities. Materials and Methods: Patients with suppurative otitis media attending Ear, Nose and Throat Department were included in this study. Patients were given structured questionnaire to determine their health seeking behaviour and health related practices. Results were tabulated and compared with literature. Results: 33.67% of pts did not seek health care services- most were males, in age group 20-39 yrs with education up to class 10 and in- come less than Rs 10,000 per month. 29% patients had only ear dis- charge and were unaware of their hearing handicap. Awareness about complication was seen in less than 15% patients. Conclusion: Majority of respondents had good and positive atti- tudes and practices regarding health seeking behaviour. The lack of appropriate knowledge, perception and erroneous practices stresses the importance of specific health education to the popula- tion. There is need to improve the community's awareness for the care of ear infections.